Apathy in Elderly Nondemented Patients With Parkinson's Disease: Clinical Determinants and Relationship to Quality of Life. (December 2013) - Skorvanek, Matej; Rosenberger, Jaroslav; Gdovinova, Zuzana; Nagyova, Iveta; Saeedian, Radka Ghorbani; Groothoff, Johan W.; Dijk, Jitse P.
Objectives: To describe the prevalence and clinical determinants of apathy in elderly nondemented patients with Parkinson's disease (PD) and their relationship to quality of life (QoL). Methods: A total of 106 nondemented elderly patients with PD were examined using the Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS), Starkstein Apathy Scale, Hospital Anxiety and Depression Scale, Beck Depression Inventory-II, and 39-item Parkinson's disease quality of life questionnaire. Results: Apathy was present in 54% of the studied population. Factors associated with apathy were higher depression scores and a lower daily levodopa equivalent dose. Longer disease duration, higher motor MDS-UPDRS subscore, and higher depression and anxiety scores, but not apathy, were found to be associated with worse QoL. Conclusions: Although apathy does not seem to be an independent predictor of worse QoL specifically in elderly patients with PD, it remains very relevant, as its presence increases caregiver burden. Both depression and potential dopaminergic treatment underdosing can be properly managed, thus potentially reducing the prevalence and severity of apathy in a proportion of the apathetic patients with PD.